2013
DOI: 10.1071/mf12151
|View full text |Cite
|
Sign up to set email alerts
|

Influence of monsoon-driven hydrographic features on siphonophore assemblages in the Taiwan Strait, western North Pacific Ocean

Abstract: The spatial patterns of siphonophores were analysed in relation to local hydrographic features during two different monsoon seasons (the north-easterly monsoon in winter v. the south-westerly monsoon in summer) in the Taiwan Strait. Forty-eight species were identified, with five types of calycophoran siphonophores (Lensia subtiloides, Chelophyes appendiculata, Chelophyes contorta, Bassia bassensis, and Diphyes chamissonis) being most common in both seasons. Significantly higher abundances of four of the five c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…A diverse community of pelagic cnidarians was found in both the Celebes and Sulu Seas in February 2000, during the winter monsoon season. Pelagic cnidarians collected in both Seas were typical of the tropical and subtropical Indo-Pacific (Daniel, 1985;Zhang, 1979;2005;Gao et al, 2002, Hsieh et al, 2013. However, due to the limited knowledge of this area, this represents the first record from these tropical marginal seas for many species, especially in the mesopelagic zone.…”
Section: Discussionmentioning
confidence: 92%
“…A diverse community of pelagic cnidarians was found in both the Celebes and Sulu Seas in February 2000, during the winter monsoon season. Pelagic cnidarians collected in both Seas were typical of the tropical and subtropical Indo-Pacific (Daniel, 1985;Zhang, 1979;2005;Gao et al, 2002, Hsieh et al, 2013. However, due to the limited knowledge of this area, this represents the first record from these tropical marginal seas for many species, especially in the mesopelagic zone.…”
Section: Discussionmentioning
confidence: 92%
“…Otherwise the species observed here from the CPO have all been recorded previously in the Pacific Ocean (Alvariño, 1971; Pagès et al , 1990). Species such as A. eschscholtzii , Abylopsis tetragona , B. bassensis , C. appendiculata , C. contorta , E. spiralis , M. atlantica , S. chuni and S. quadrivalvis are widely distributed in tropical waters of the Eastern Pacific (Gasca & Suárez, 1992a, b) and the Caribbean (Gasca, 1999), further west in the tropical Pacific (Pagès et al , 1990; Lo et al , 2012, 2014; Hsieh et al , 2013) as well as cooler Chilean (Palma, 1999; Palma & Silva, 2004) and Peruvian (Ayón et al , 2008) waters. Most species of siphonophore have a near global distribution (Mackie et al , 1988), with all of the species found here reported from either the Atlantic (Pugh, 1999) or the Indian oceans (Daniel, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…In the Sagami Bay, Grossmann and Lindsay [20] observed that the siphonophore communities could be related to the different water masses in the Bay, with an important influence of lateral transport of both tropical and subarctic species into the Bay by the different water masses. In the TS, it has been revealed that the distribution pattern of siphonophore assemblages was closely related to the hydrographic features, influenced by the dynamic nature of the currents in the area, with temperature, salinity, and zooplankton biomass being the three most important factors [21] . López-López et al [22] found higher abundance of gelatinous carnivore zooplankton one month after the occurrence of a strong typhoon in northern Taiwan.…”
Section: Introductionmentioning
confidence: 99%